Refugees, Europe, Death and COVID-19 - Gržinić, Marina (Identities: Journal for Politics, Gender and Culture, 2020)
Author(s): Marina Gržinić Title (English): Refugees, Europe, Death and COVID-19 Journal Reference: Identities: Journal for Politics, Gender and Culture Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 10-13 Page Count: 4 Citation (English): Marina Gržinić, “Refugees, Europe, Death and COVID-19,” Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 1 (Summer 2020): 10-13.